When Is an Adolescent an Adult? Assessing Cognitive Control in Emotional and Nonemotional Contexts. (April 2016) - Cohen, Alexandra O.; Breiner, Kaitlyn; Steinberg, Laurence; Bonnie, Richard J.; Scott, Elizabeth S.; Taylor-Thompson, Kim; Rudolph, Marc D.; Chein, Jason; Richeson, Jennifer A.; Heller, Aaron S.; Silverman, Melanie R.; Dellarco, Danielle V.; et al.
An individual is typically considered an adult at age 18, although the age of adulthood varies for different legal and social policies. A key question is how cognitive capacities relevant to these policies change with development. The current study used an emotional go/no-go paradigm and functional neuroimaging to assess cognitive control under sustained states of negative and positive arousal in a community sample of one hundred ten 13- to 25-year-olds from New York City and Los Angeles. The results showed diminished cognitive performance under brief and prolonged negative emotional arousal in 18- to 21-year-olds relative to adults over 21. This reduction in performance was paralleled by decreased activity in fronto-parietal circuitry, implicated in cognitive control, and increased sustained activity in the ventromedial prefrontal cortex, involved in emotional processes. The findings suggest a developmental shift in cognitive capacity in emotional situations that coincides with dynamic changes in prefrontal circuitry. These findings may inform age-related social policies.